+0  
 
0
115
2
avatar+202 

The roots of y^2 + 5y - 11 = 0 are a and b. Find (a + 3)(b + 3).

 Aug 3, 2020
 #1
avatar
0

The roots a and b are \(\frac{-5 \pm \sqrt{69}}{3}\)

 

so (a + 3)(b + 3) = \((-\frac{5 + \sqrt{69}}{3} + 3)(-\frac{5 - \sqrt{69}}{3} + 3) = -21\)

 Aug 3, 2020
 #2
avatar+2152 
0

Adding onto Guest's answer:

 

You use the quadratic formula to find the roots of y^2+5y-11.

 

The quadratic formula is:

-b+-sqrt(b^2-4ac) / 2a

 

So, in this case, a=1, b=5, and c=-11

 Aug 3, 2020

19 Online Users

avatar
avatar
avatar
avatar